The Roles of Educators (Didactic, Reflective, Affective Roles) to Enhance Motivation to Learn Social Science During the Covid-19 Pandemic at Islamic Secondary Schools (MTs) in Tulungagung-Indonesia - Nur Isroatul Khusna; Dwi Astuti Wahyu Nurhayati; Jani Jani; Binti Maunah; Linda Mayasari (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2021)
During the COVID-19 pandemic, student learning activities concerning learning interests gradually decreased. As a result, various efforts are needed to increase students' motivation in every learning activity. This study aims to describe the application of educators' roles (didactic, reflective, affective roles) and to discover the inhibiting factors educators face to enhance motivation to learn social science. The approach used in this study was a descriptive qualitative approach. The data sources in this study included primary sources interviewed. Meanwhile, secondary sources were the documents obtained at the research sites. These data were collected by conducting observation, interviews, and documentation. The study results indicate that the educators used learning resources such as textbooks and worksheets. The technique to deliver the materials was summarizing the materials in the form of Word/PDF or explaining the materials through voice notes. The instructional media used by the educators were pictures, WhatsApp, E-learning, and Google Forms. The educators implemented the scientific learning approach in applying for the reflective role. The instructional models adopted by the educators were discovery learning and problem-based learning. In addition, the educators conducted evaluations at the beginning or end of learning to determine the level of success. The educators provided good examples and continuous advice in applying for the affective role. The inhibiting factors faced by the educators include lack of learning interest, difficulty understanding the material and financial constraints, and inadequate school facilities.